IMPACT OF THE 2022 BALI ARTS FESTIVAL (PKB) AT THE DENPASAR ART CENTER ON THE ECONOMY AND TOURISM SECTOR IN BALI - Gede Budi Puja Arka Dana; Komang Pera Apriwati; I Nyoman Fajar Pramana (UHN IGB Sugriwa Denpasar, 2023)
The open-air Ardha Candra building has become a special place for the people of Yogyakarta and has also contributed valuable cultural heritage to Indonesia. The specific research objectives will depend on the discipline and the need for deeper research. MICE (Meeting, Incentive, Convention, Exhibition) has become an integrated and efficient concept in organizing various types of events. The use of the Ardha Candra open stage in MICE events offers several advantages. First, this open location provides a unique experience for event participants with a refreshing natural atmosphere and beautiful scenery. Second, the open stage provides flexibility in space arrangement and event layout, allowing adjustments according to different event needs. Furthermore, the use of advanced technology in managing sound, lighting, and the layout of the Ardha Candra open stage can enhance the efficiency and quality of MICE events. High-quality sound systems and creative lighting create an impressive atmosphere, while flexible stage layouts allow for optimal use of space. In this article, we will also discuss several case studies of MICE events held on the Ardha Candra open stage. Research results show that the use of this open stage has successfully increased participant participation, improved brand image, and created unforgettable experiences.